2020
DOI: 10.3389/fimmu.2020.01170
|View full text |Cite
|
Sign up to set email alerts
|

Psycho-Neuroendocrine-Immune Interactions in COVID-19: Potential Impacts on Mental Health

Abstract: Coronavirus disease 2019 (COVID-19) is caused by the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). The impacts of the disease may be beyond the respiratory system, also affecting mental health. Several factors may be involved in the association between COVID-19 and psychiatric outcomes, such as fear inherent in the pandemic, adverse effects of treatments, as well as financial stress, and social isolation. Herein we discuss the growing evidence suggesting that the relationship between SARS-CoV-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
118
0
45

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 150 publications
(163 citation statements)
references
References 144 publications
0
118
0
45
Order By: Relevance
“…Individuals with significantly poorer mental wellbeing (sten scores higher than 7 in GHQ 28) experience stress more intensely than others and use rather unsuitable coping strategies (denying problems, emotional discharge, taking substances, giving up, and blaming themselves for the situation). It can be cautiously assumed that these individuals, who are most likely to experience high levels of anxiety, prefer passive counter-measures (“freezing”) as a behavioural (and endocrine) pattern in situations where danger is perceived as inevitable but relatively distant [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with significantly poorer mental wellbeing (sten scores higher than 7 in GHQ 28) experience stress more intensely than others and use rather unsuitable coping strategies (denying problems, emotional discharge, taking substances, giving up, and blaming themselves for the situation). It can be cautiously assumed that these individuals, who are most likely to experience high levels of anxiety, prefer passive counter-measures (“freezing”) as a behavioural (and endocrine) pattern in situations where danger is perceived as inevitable but relatively distant [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…This condition is the body’s natural physical and emotional response to the stimuli. According to H. Selye’s theory, in case of a prolonged stressful situation—even if its strength is not too great—our body’s resources will drastically decrease [ 41 ], which will eventually result in the occurrence of somatic and/or mental symptoms [ 22 , 42 ]. The second part of the research can provide interesting findings in this area.…”
Section: Discussionmentioning
confidence: 99%
“…Neurological and psychiatric manifestations have also been reported in patients with COVID-19, 5,6 and a cross-sectional study recently reported that patients with severe COVID-19 had significantly higher plasma biomarker levels of neuronal damage and glial activation. 7 In addition, SARS-CoV-2 was detected in the cerebrospinal fluid and brain of patients with COVID-19, 8,9 as well as in neurons of human-induced pluripotent stem cell (iPSC)-derived Brainspheres.…”
Section: Dear Editormentioning
confidence: 91%
“…The breakdown of BRB can also be applied to the hypothetical systemic hematogenous route, which has been described as a possible pathway for SARS-CoV-2 entry into CNS. 5 Accordingly, we hypothesize that this route could also be related to the arrival of SARS-CoV-2 in the retinal tissue beyond its local contamination in the eye, since the virus was identified in the retina by Casagrande et al, 1 but still, there is a lack of evidence sustaining the possibility of direct ocular infection, and no study has yet shown SARS-CoV-2 in the cornea. Therefore, there are two possible mechanisms for systemic hematogenous pathway: (1) through direct infection of microvascular endothelial cells that express ACE2 and CD147, (2) through infected leukocytes that can cross the BRB and carry the virus into retina, a kind of Trojan horse mechanism.…”
Section: Hematogenous Routementioning
confidence: 97%
See 1 more Smart Citation